Surviving prematurity: retrospective longitudinal study of multisystem consequences in preterm-born individuals from infancy to adolescence - Ruta Morkuniene; Ruta Levuliene; Vilmantas Gegzna; Egle Marija Jakimaviciene; Janina Tutkuviene (BMC Pediatrics)
Abstract Background Prematurity is linked to diverse and significant health outcomes, but a comprehensive understanding of its long-term multisystem impacts remains limited. Methods Retrospective longitudinal cohort study on 417 preterm children born between 2000 and 2015 explores the incidence, dynamics, and interrelationships of health conditions from infancy to adolescence. Data on 1818 diagnoses, categorised by birth weight (BW) and gestational age (GA) and documented according to ICD-10, were analysed using non-parametric tests and negative binomial regression models. Results Most diagnoses occurred by age 7, with eye diseases, congenital malformations, and infections most prevalent, but the greatest disparities with the general population were in blood, nervous system, mental, and neoplastic diseases. Lower BW significantly correlated with higher mean disease counts and greater diversity of health conditions across various ICD-10 chapters, while GA showed less pronounced associations. Children in "Extremely and very low," "Low," and "Sub-optimal" BW categories exhibited 1.77, 1.50, and 1.34 times more diseases, respectively, than those in the "Normal" BW category. Unique and highly individual patterns of disease co-occurrence were observed, increasing in complexity as BW decreased. Conclusions The highest disease burden for preterm-born individuals occurred by age 7, with lower BW linked to greater health complexity and unique comorbidities.